Sinergi Ekonomi dan Hukum Tata Negara Islam dalam Mewujudkan Kesejahteraan Umat: Perspektif Maqāṣid al-Syarī‘ah - Putra, Andika Dwi; Hidayat, Muhammad Nur; Kurniati (CV Global Research Publication, 2025)
Throughout Islamic civilization, the synergy between economics and constitutional law has played a crucial role in achieving community welfare based on the principles of Maqāṣid al-Syarī‘ah. This study aims to analyze the contribution of Islamic constitutional law to the development of an equitable Islamic economic system. The research employs a qualitative descriptive approach through literature studies, examining various sources related to Islamic constitutional law and Islamic economics. The findings indicate that the principles of Islamic constitutional law, such as justice (‘adl), consultation (syurā), trust (amānah), and the protection of individual and communal economic rights, significantly influence the formation of a more inclusive and sustainable economic system. The implementation of Maqāṣid al-Syarī‘ah in Indonesia’s economic policies is reflected in regulations on zakat, Islamic banking, halal investment, and resource management aimed at public welfare. However, key challenges remain, including the harmonization of Islamic law with positive law and disparities in wealth distribution. Strengthening Maqāṣid al-Syarī‘ah-based policies is therefore necessary to ensure that the Islamic economic system can optimally contribute to improving societal well-being.